2007
DOI: 10.1007/s00125-007-0716-y
|View full text |Cite
|
Sign up to set email alerts
|

A Palaeolithic diet improves glucose tolerance more than a Mediterranean-like diet in individuals with ischaemic heart disease

Abstract: Aims/hypothesis Most studies of diet in glucose intolerance and type 2 diabetes have focused on intakes of fat, carbohydrate, fibre, fruits and vegetables. Instead, we aimed to compare diets that were available during human evolution with more recently introduced ones. Methods Twenty-nine patients with ischaemic heart disease plus either glucose intolerance or type 2 diabetes were randomised to receive (1) a Palaeolithic ('Old Stone Age') diet (n=14), based on lean meat, fish, fruits, vegetables, root vegetabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
262
4
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(284 citation statements)
references
References 51 publications
11
262
4
7
Order By: Relevance
“…Equally, in a randomized cross-over study of three months duration, diabetic patients receiving a Paleolithic diet (lean meat, fish, fruit, vegetables, root vegetables, eggs, and nuts) showed a reduction in body weight, BMI and waist circumference, lower HbA1c, TAG and diastolic blood pressure, and an improvement in glycaemic control [12]. These studies are further supported by Lindeberg et al [13] who reported that patients with ischemic heart disease concomitant with glucose intolerance or type 2 diabetes had a large improvement in insulin sensitivity and glucose tolerance when receiving a Paleolithic diet. Even in non-human studies the Paleolithic diet has been successfully used as a model to explain modern disease.…”
Section: Insulin Resistance and Our "Primitive" Genomementioning
confidence: 66%
“…Equally, in a randomized cross-over study of three months duration, diabetic patients receiving a Paleolithic diet (lean meat, fish, fruit, vegetables, root vegetables, eggs, and nuts) showed a reduction in body weight, BMI and waist circumference, lower HbA1c, TAG and diastolic blood pressure, and an improvement in glycaemic control [12]. These studies are further supported by Lindeberg et al [13] who reported that patients with ischemic heart disease concomitant with glucose intolerance or type 2 diabetes had a large improvement in insulin sensitivity and glucose tolerance when receiving a Paleolithic diet. Even in non-human studies the Paleolithic diet has been successfully used as a model to explain modern disease.…”
Section: Insulin Resistance and Our "Primitive" Genomementioning
confidence: 66%
“…On the other hand, a Paleolithic diet (i.e. a diet consisting of lean meat, fish, shellfish, fruits and vegetables, roots, eggs and nuts, but not grains, dairy products, salt or refined fats and sugar) was associated with marked improvement of glucose tolerance while control subjects who were advised to follow a Mediterranean-like diet did not significantly improve their glucose tolerance despite decreases in weight and waist circumference [13] .…”
Section: Mediterranean Diet and Diabetesmentioning
confidence: 96%
“…Consensus dietary advice places considerable emphasis on the inclusion of breads and baked goods, and it is arguable that this retention of flour-derived foods may be responsible for the poor consensus performance versus paleolithic diets in the clinical trials carried out to date (17)(18)(19)(20)(21)58,59). The omnipresence of flour, breads and baked goods in most nutrition research has prevented the proper investigation of the concentration-health relationship for refined foods in 'sensitized' populations, which anecdotal observations from those eating no refined foods indicate may be non-linear.…”
Section: Obesity As a Process Of Sensitizationmentioning
confidence: 99%